Lupus Anticoagulant Activity Is Frequently Dependent on the Presence of β2-Glycoprotein I - Oostin, Janine D; Derksen, Ronald H W M; Entjes, H Tanja I; Bouma, Bonno N; de Groot, Philip G (Thrombosis and Haemostasis, 1992)
Antiphospholipid antibodies (aPL) are defined by anticardioli-pin antibody (aCL) ELISA and prolongation of phospholipid dependent coagulation assays (lupus anticoagulant; LAC). For the binding of aCL to cardiolipin a cofactor, β2-glycoprotein I (β2-GPI), is necessary. We have investigated whether the same cofactor is essential for LAC activity. Plasma from 6 LAC positive patients and 3 controls was depleted from β2-GPI by means of affinity chromatography. From the 6 LAC positive plasmas, 4 became LAC negative (tested with dRWT) when β2-GPI was depleted and became positive again when purified β2-GPI (200 μg/ml) was added. A dose response curve showed that addition of 50 μg/ml β2-GPI to β2-GPI deficient patient plasma, led to a positive dRWT. Depletion of, and addition of β2-GPI to plasma from controls had no effect on the dRWT. Measurement of β2-GPI plasma levels in 19 LAC positive patients, 40 LAC negative patients and 15 controls showed no difference in β2-GPI levels.These results show that a combination of aPL and β2-GPI is essential not only for binding to cardiolipin, but also for LAC activity and imply that low β2-GPI levels (<50 μg/ml) can lead to false negative LAC tests. These observations may lead to new insights in the pathophysiological complications associated with aPL.